Categories of Analysis and Categories of Practice since the Tajik Civil War - Sophie Roche (Antropologia, 2013)
They said, ‘we won’t say anything to Kyrgyz people, you can come back,’ and my husband believed. Akai Ibrohim, the one who just died, people said that Afghans had made him a slave, that they took his wife and daughter, and we believed. Today they say we came back because of our money. […] We came so that our children should not suffer, let’s go to our homeland we thought, but nobody asked in this war whether you have weapons or not, whether you are guilty or not. During this war, those who had no sins came back, those who were guilty didn’t go, they knew they were guilty and left; those without sin came and were taken instead of the guilty. […] We came to Shahrituz and they made us climb a truck, bigger than our house. They brought us to this school PTU and picked out the men. […] If you were Tajik, that’s it, you died.